Merry Christmas, Alex Cross - Patterson, James, 1947- (New York : Little, Brown and Co., 2012)
It's Christmas Eve and Detective Alex Cross is called away from his family to resolve a horrific hostage situation that is spiraling out of control.
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American detectives -- Fiction; Mystery -- Fiction; Large type books; Washington (D.C.) -- Fiction